(untitled) (The Journal of Plant Protection Sciences, 2021)
Efficacy of neem (Azadirachta indica A.Jass), soap nut (Sapindus trifoliatus L.) and their formulations and Malathion as standard insecticide were evaluated against the rice bug (Leptocorisa oratorius Fabr.) during 2000-2001 on the basis of per cent reduction under field condition. The per cent reduction in number of rice bug adults due to neem seed kernel powder, neem seed kernel powder + multani powder, multani powder, neem leaf powder, neem leaf powder + multani powder, neem leaf powder + ash, soap nut kernel powder, soap nut kernel powder + multani powder tested as dust were found to be 24.44, 14.78, 5.65, 17.06, 11.88, 6.54, 18.18 and 15.01 respectively for exposure period of ten days. The order of efficacy of the botanicals and their formulations were malathion followed by neem seed kernel powder, soap nut kernel powder, neem leaf powder, neem seed kernel powder + multani powder, soap nut kernel powder + multani powder, neem leaf powder + multani powder, neem leaf powder + ash, multani powder for the exposure period of 3, 7 and 10 days respectively.